By honor bound : two Navy SEALs, the Medal of Honor, and a story of extraordinary courage - Norris, Tom (Thomas R.), 1944-; Thornton, Mike (Michael E.), 1949-; Couch, Dick, 1943- (St. Martin's Press, 2016)
"Two living American heroes discuss how they grew up very differently, entered military service and the Navy SEAL teams for vastly different reasons, and were thrown together for a single combat mission- a mission that would define their lives from that day forward,"--NoveList.